Effects of lower doses of cloprostenol intramuscular or into vulvar submucosa on estrus induction and pregnancy rates in Nelore cows - Chacur, Marcelo George Mungai; Ferreira Aurélio, Paulo Tiago; Scalon Jr., Orivaldo; Inague, Leandro; Scalon, Luis Fernando; Do Nascimento Kronka, Sérgio [UNESP] (Universidade Estadual de Londrina, 2010)
The present study aims to compare the effects of lower doses of cloprostenol intramuscular (IM) or into vulvar submucosa (IVS) on estrus induction and pregnancy rate in Nelore cows. A total of 100 cycling Nelore cows with body condition score (BCS 3.5) 1 to 5 scale (Radostitis; Blood, 1986) and 170±11 days postpartum. Females were randomly divided in 5 groups (N=20) G1 to G5 and treated with cloprostenol (Ciosin®) on day 0 (D0) and on day 11 (D11) if not detected in estrus. Cows were injected with 500μg IM (G1), 250μg IM (G2), 125μg IM (G3), 250μg IVS (G4) and 125μg IVS (G5). Estrus was observed twice a day and the females artificially inseminated 12 hours after heat detection. There was no statistical difference (P>0.80) between groups in the estrus induction (first injection to estrus interval): 16/20-96.00 hours (G1), 13/20-90.42 hours (G2), 10/20-84.45 hours (G3), 15/20-87.86 hours (G4), 12/20-81.25 hours (G5) and second injection (P>0.10): 4/20-67.50 hours (G1), 7/20-85.50 hours (G2), 10/20-57.00 hours (G3), 5/20-70.60 hours (G4), 8/20-60.00 hours (G5). There was no statistical difference (0.65ns) between groups in the pregnancy rates: 40% (G1), 45% (G2), 50% (G3), 40% (G4), 40% (G5). The results demonstrate that the treatments with lower doses of cloprostenol intramuscular or into vulvar submucosa may be used to induce heat with similar pregnancy rates in cycling Nelore cows with good body condition.
Efeitos de baixas doses de cloprostenol via intramuscular ou submucosavulvar na indução do estro e taxas de prenhez em vacas Nelore
Keywords: Artificial insemination; Bos taurus indicus; Micro doses; Prostaglandin; Zebu cows